IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT THROUGH MULTICULTURAL AND MULTI-RELIGIOUS LOCAL WISDOM MODULE AT SMP NEGERI 20 TANGERANG - Rahmawati, Destiani; Juniardi, Yudi; Hidayatullah, Hidayatullah (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The theme of local wisdom in learning Islamic Religious Education, it is hoped that students can gain a more holistic understanding of religious values and in line with the values of Pancasila and local wisdom and will help strengthen students' character and national identity as citizens of the One and Only God, Justice, and Civilized in accordance with the values of Pancasila, while still respecting the cultural and religious diversity that exists in Indonesia. Purpose: The three goals of this study are to: (A) explain the process of identifying P5's theme; (B) explain how P5 is implemented with regard to the theme of local knowledge; and (C) describe P5's evaluation with regard to this theme. Method: This study's methodology employs a qualitative-descriptive approach, looking at procedures, visualizing events, and summarizing events based on information gathered from interviews and observation. By searching for additional data to support the findings and verifying the information the researcher received from the data supplier, triangulation can be used to assess the validity of the data in this study. In this study, data reduction, data visualization, and conclusion-making are used in data analysis. Result: The findings of this study are as follows: (A) the Pancasila Student Profile Strengthening Project theme is decided upon in accordance with a school agreement; and (B) all grade VIII students at SMP Negeri 20 Kota Tangerang implemented local wisdom theme projects under the guidance of a team of coordinators or teachers. Conclusion: The stages of introduction, contextualization, action, reflection, and follow-up are the first ones that it goes through during implementation. Evaluations are then conducted in order to prepare for the next round of project improvements